Religiosity And the Fraud Triangle as A Cause of Student Academic Fraud in Online Lectures - Christina Sososutiksno; Jefry Gasperz; Adonia Anita Batkunde (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2023)
This study aims to test and analyze the influence of moderation of religiosity variables on the impact of independent variables, namely the dimension of the fraud triangle (Pressure, Opportunity, and Rationalization) to dependent variables (student academic cheating actions) during online lectures. This research is essential because the potential for student academic fraud can arise due to the three dimensions of the fraud triangle. This research is a type of quantitative research using questionnaires for data collection. The population in this study were undergraduate students of the Accounting Department, Faculty of Economics and Business, Pattimura University, Ambon. The sample in this study was 92 respondents from the class of 2017-2019. The results of this study show that the three dimensions of the fraud triangle have a direct and significant influence on increasing student academic fraud. Furthermore, the role of the Religiosity variable in moderating (weakening) the impact of the fraud triangle dimension on student academic cheating actions showed positive results for the Pressure and Opportunity variables. Meanwhile, the Rationalization variable cannot moderate or cannot weaken the Student's Academic Cheating Action because it produces negative values